TANTANGAN PERKEMBANGAN TEKNOLOGI MELALUI METODE PEMBAYARAN QRIS BAGI UMKM DAN KONSUMEN - Andhika, Muchammad Milladi; Ariani, Mintarti; Budiarto, Bambang (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to determine how the application of the QRIS payment method is currently being implemented by MSMEs, as well as to identify various obstacles and barriers faced by MSMEs in developing and using the QRIS payment method. Data were obtained through in-depth interviews with several informants involved in the implementation of QRIS. The data analysis process was carried out using the open coding method, where interview transcripts were processed into a table, numbered sequentially, and highlighted based on relevant keyword categories. The categories analyzed included the development of QRIS as a payment method, positive impacts, and negative challenges faced in its use. The results indicate that although QRIS provides ease in transactions, challenges related to technology adoption still need to be addressed. Positive responses from consumers and MSME actors show great potential for the development of QRIS as a more inclusive and efficient payment system. This study is expected to provide insights into the development of QRIS and its contribution to enhancing financial inclusion in Indonesia.